Pengaruh Kualitas Pelayanan dan Inovasi Produk pada Boy's Cake and Bakery Mojolaban, Sukoharjo - Arifah, Mutia Nur; Suryoko, Sri (Universitas Diponegoro, 2021)
Abstract: In this study, specifically discussing the sales of Boy's Cake and Bakery in 2016 - 2019, sales were quite volatile, because in the last year, 2019, there was a significant decrease. This study is to determine Service Quality (X1) and Product Innovation (X2) on Purchasing Decisions (Y) at Boy's Cake and Bakery. Researchers used explanatory research type and purposive sampling and accidental sampling techniques. The results showed that the service quality variable (X1) had a positive effect on the purchase decision for Boy's Cake and Bakery (Y), the product innovation variable (X2) had a positive effect on the purchase decision at Boy's Cake and Bakery (Y) and the service quality variable and product innovation were together have a positive and important effect on purchasing decisions for Boy's Cake and Bakery. The suggestions given to Boy's Cake and Bakery, the variable service quality from Boy's Cake and Bakery is good, but Boy's Cake and Bakery needs to maintain and improve the quality of service provided, especially in terms of convenience store room, delivery service made easier with minimal restrictions on delivery , has a unique characteristic of product taste, pays more attention to product availability, accelerates service for consumers, is more familiar with product specifications, pays more attention to returning to operating hours, simplifies communication between consumers and employees.Keywords: Service Quality; Product Innovation; Purchase Decision Abstrak: Dalam penelitian ini secara khusus membahas mengenai penjualan Boy’s Cake and Bakery tahun 2016 – 2019 mengalami penjualan yang cukup fluktuatif, karena di tahun terakhir yaitu tahun 2019 terlihat penurunan yang cukup signifikan. Penelitian ini untuk mengetahui Kualitas Pelayanan (X1) dan Inovasi Produk (X2) terhadapa Keputusan Pembelian (Y) di Boy’s Cake and Bakery. Peneliti menggunakan tipe penelitian explanatory research dan Teknik Purposive Sampling dan Accidental Sampling. Hasil penelitian menunjukkan bahwa Variabel kualitas pelayanan (X1) berpengaruh positif terhadap keputusan pembelian Boy's Cake and Bakery (Y), Variabel inovasi produk (X2) berpengaruh positif terhadap keputusan pembelian di Boy's Cake and Bakery (Y) dan Variabel kualitas pelayanan dan inovasi produk secara bersama-sama berpengaruh positif dan penting terhadap keputusan pembelian Boy's Cake and Bakery. Saran yang diberikan kepada Boy's Cake and Bakery variabel kualitas pelayanan dari Boy’s Cake and Bakery sudah baik, namun Boy’s Cake and Bakery perlu mempertahankan dan meningkatkan lagi kualitas pelayanan yang diberikan, terutama dalam hal kenyamanan ruangan toko layanan pesan antar yang dipermudah dengan pembatasan minimal pengantaran, memiliki ciri khas cita rasa produk yang unik, lebih memeperhatikan kesediaan produk, memepercepat layanan untuk konsumen, lebih mngenal lagi spesifikasi produk, lebih memperhatikan kembali kepada jam operasional, memepermudah lagi komunikasi antara konsumen dan karyawan. Kata Kunci: Kualitas Pelayanan; Inovasi Produk; Keputusan Pembelian